Addressing key features involved in bioactive extractability of vigor prickly pears submitted to high hydrostatic pressurization. (27th July 2019) - Gómez‐Maqueo, Andrea; Ortega‐Hernández, Érika; Serrano‐Sandoval, Sayra N.; Jacobo‐Velázquez, Daniel A.; García‐Cayuela, Tomás; Cano, M. Pilar; Welti‐Chanes, Jorge
Abstract: Prickly pears are relevant sources of bioactive compounds with potential biological activities. However, to become bioaccessible, these compounds must be released from the food matrix. High hydrostatic pressure (HHP) may contribute to bioaccessibility by promoting the liberation of bioactive constituents from their intracellular compartments. Our aim was to address key features involved in the high hydrostatic pressurization (18–34°C) of prickly pear fruits to promote bioactive extractability. We studied the effects of the come‐up time (CUT) and holding time (HT; 5 min) at low (60, 100, and 150 MPa) and high pressures (400, 500, and 600 MPa) in whole‐pressurized and sliced‐pressurized fruits. The best overall treatment was found by submitting whole prickly pears to 500 MPa during the CUT. In this treatment, 104.0, 150.8, and 100.5% retention of betalains, phenolics, and ascorbic acid were observed in peels; and 130.7, 121.4, and 128.4% retention were observed in pulps. Practical Applications: Prickly pears are abundant in Mexico and represent potential sources for low‐cost functional foods because of their health properties. In a country constantly affected by obesity and diabetes incidence, the continuous search for nutritious and health‐promoting processed foods should not be taken lightly. The use of HHP pre‐treatments to enhance the functionality of local vegetable products as a goal, and no longer as a side effect represents a strong potential application of this non‐thermal technology. In the next years, new sustainable processes involving HHP for the manufacturing of functional foods are expected to grow and be implemented in emerging markets such as Latin America. Abstract :